2001
DOI: 10.1161/01.hyp.37.2.490
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Renal Vascular Fibrosis by Endothelin Receptor Antagonism

Abstract: Abstract-In previous studies, we have observed that endothelin participates in the progression of renal vascular and glomerular fibrosis during hypertension by activating collagen I gene synthesis. The present study investigated whether administration of endothelin receptor antagonists leads to the regression of renal sclerotic lesions. Experiments were performed in transgenic mice harboring the luciferase gene under the control of the collagen I-␣2 chain promoter. Hypertension was induced by long-term inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 39 publications
6
55
1
4
Order By: Relevance
“…We observed that, despite a successful resolution of the stenosis, a combined ET-A/B blockade strategy after PTRAS did not improve renal function, MV damage, or nephrinuria. On the contrary, our results suggest that ET-A/B blocker therapy significantly diminished the beneficial effects of PTRAS or ET-A receptor blockade on the stented kidney, implying that ET-B receptors are necessary to protect the kidney 28 It is possible that addition of ET-B receptor antagonism after PTRAS might have triggered AKI 29 or exacerbated eventual reperfusion injury 30 that was minimized in this model by single ET-A blockade, suggesting a potential interaction between both receptors in controlling renal damage. 9 Another possibility is that the addition of ET-B blockade exacerbated MV remodeling 31 and thus, intrarenal MV resistance in the poststenotic kidney, which may have also played a role later in the minimal or even negative changes in RBF or GFR 4 weeks after PTRAS.…”
Section: Discussioncontrasting
confidence: 76%
“…We observed that, despite a successful resolution of the stenosis, a combined ET-A/B blockade strategy after PTRAS did not improve renal function, MV damage, or nephrinuria. On the contrary, our results suggest that ET-A/B blocker therapy significantly diminished the beneficial effects of PTRAS or ET-A receptor blockade on the stented kidney, implying that ET-B receptors are necessary to protect the kidney 28 It is possible that addition of ET-B receptor antagonism after PTRAS might have triggered AKI 29 or exacerbated eventual reperfusion injury 30 that was minimized in this model by single ET-A blockade, suggesting a potential interaction between both receptors in controlling renal damage. 9 Another possibility is that the addition of ET-B blockade exacerbated MV remodeling 31 and thus, intrarenal MV resistance in the poststenotic kidney, which may have also played a role later in the minimal or even negative changes in RBF or GFR 4 weeks after PTRAS.…”
Section: Discussioncontrasting
confidence: 76%
“…3,17,18 Timely blockade of angiotensin II action (angiotensin-converting enzyme inhibitors or angiotensin type 1 receptor antagonists) can promote reversal of renal lesions and ultimately prevent the progression to ESRD in animal models. 3,19,20 However, renin-angiotensin system blockers do not exhibit the same efficiency in arresting or reversing chronic renal disease progression in humans, making the identification of novel targets for therapy urgent. 21,22 The present study examined whether periostin could be such a target.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin receptor antagonism, introduced after the appearance of fibrotic lesions, reduced mortality (Table 1); moreover, the treated animals displayed a less severe degree of glomerular lesions even compared with those at the beginning of the treatment, suggesting thus that renal vascular fibrosis could regress by ET-1 antagonism. 31 However, this regression was partial and less efficient compared to the consequences of angiotensin II antagonism.…”
Section: Mediators Of the Angiotensin II Actionmentioning
confidence: 99%